Lauroyl hyaluronan films for local drug delivery: Preparation and factors influencing the release of small molecules - Chmelař, Josef; Brtková, Barbora; Laštovičková, Lenka; Bažantová, Jana; Hermannová, Martina; Kulhánek, Jaromír; Mrázek, Jiří; Velebný, Vladimír (International journal of pharmaceutics, 2021)
Lauroyl derivatives of hyaluronan are safe and biodegradable materials that seem promising for application in medicine. However, their potential in the field of drug delivery was not yet explored. We thus prepared lauroyl hyaluronan films loaded with various drugs and studied the effects of lauroyl hyaluronan properties, drug hydrophobicity and medium composition on the drug release. Since biomolecules will always be present in real clinical applications, media supplemented by albumin were also included. The amphiphilic character of lauroyl hyaluronan enabled convenient loading of the films by both hydrophilic and hydrophobic drugs. Dominant factors influencing drug release were drug hydrophobicity and the presence of albumin. Hydrophilic diclofenac was released rapidly in all cases, while triclosan with medium hydrophobicity exhibited slower release sensitive to other parameters, reaching equilibrium values in the used experimental setup. The release of hydrophobic octenidine into pure buffer was almost negligible, but the addition of albumin did promote its release. The strong effect of albumin highlights the importance of considering biomolecules in the design of release experiments.
Keywords: kyselina hyaluronová; Hyaluronic Acid; lékové transportní systémy; Albumin; uvolňování léčiv; Drug Delivery Systems; Lauroyl hyaluronan; hydrofobní a hydrofilní interakce; léčivé přípravky; Release profile; Hydrophobic and Hydrophilic Interactions; Drug delivery; Drug Liberation; Pharmaceutical Preparations; Film